Gambaran Coping Strategy pada Remaja Puteri yang Melakukan Pernikahan Dini - Fia Oktaviani; Nani Nuranisah Djamal; Imam Sunardi (Psympathic : Jurnal Ilmiah Psikologi, 2018)
The adolescents usually spent time as a student. However, there were adolescents who married early which may cause them to lose one of the most important duties in their adolescences period, such as preparing for marriage and household. Adolescents who married in early age have a new role in their life as an adult. Marriage life came with its own problems that may cause stressors. Stressors can be solved by individual’s coping strategies. Coping is the way individual deal with stressful situation. The purpose of this study was to explore the coping used by married adolescents at the age of 15-16 years old in Bandung. This study used qualitative method and phenomenology research with three key informants. The results of this study show that three subjects used emotion-focused coping more dominant than problem-focused coping. The reason was the subjects mostly use feeling and show emotional signs when they have problems.